2年生の夢(高さ2のテトレーションの0から1までの定積分)

2年生の夢(高さ2のテトレーションの0から1までの定積分)

(1)

\begin{align*} \int_{0}^{1}\frac{1}{x^{x}}dx & =\sum_{k=1}^{\infty}\frac{1}{k^{k}}\\ & =1.291\;285\;997\;062\;663\cdots \end{align*}

テトレーション表示

\[ \int_{0}^{1}\frac{1}{x\uparrow^{2}2}dx=\sum_{k=1}^{\infty}\frac{1}{k\uparrow^{2}2} \]

(2)

\begin{align*} \int_{0}^{1}x^{x}dx & =-\sum_{k=1}^{\infty}\left(-k\right)^{-k}\\ & =0.783\;430\;510\;712\;134\cdots \end{align*}

テトレーション表示

\[ \int_{0}^{1}x\uparrow^{2}2dx=-\sum_{k=1}^{\infty}\left(-k\right)\uparrow^{2}2 \]

-

\(x\uparrow^{2}n\)はクヌースの矢印表記

(1)

\begin{align*} \int_{0}^{1}\frac{1}{x^{x}}dx & =\int_{0}^{1}e^{-x\log x}dx\\ & =\int_{0}^{1}\sum_{k=0}^{\infty}\frac{\left(-x\right)^{k}\log^{k}x}{k!}dx\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!}\int_{0}^{1}x^{k}\log^{k}xdx\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!}\int_{\infty}^{0}e^{-ky}\left(-y\right)^{k}e^{-y}\left(-1\right)dy\cmt{x=e^{-y}}\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!}\int_{0}^{\infty}e^{-\left(k+1\right)y}\left(-y\right)^{k}dy\\ & =\sum_{k=0}^{\infty}\frac{1}{k!}\int_{0}^{\infty}e^{-\left(k+1\right)y}y^{k}dy\\ & =\sum_{k=0}^{\infty}\frac{1}{k!\left(k+1\right)^{k+1}}\int_{0}^{\infty}e^{-y}y^{k}dy\\ & =\sum_{k=0}^{\infty}\frac{1}{k!\left(k+1\right)^{k+1}}k!\\ & =\sum_{k=0}^{\infty}\frac{1}{\left(k+1\right)^{k+1}}\\ & =\sum_{k=1}^{\infty}\frac{1}{k^{k}} \end{align*}

(2)

\begin{align*} \int_{0}^{1}x^{x}dx & =\int_{0}^{1}e^{x\log x}dx\\ & =\int_{0}^{1}\sum_{k=0}^{\infty}\frac{x^{k}\log^{k}x}{k!}dx\\ & =\sum_{k=0}^{\infty}\frac{1}{k!}\int_{0}^{1}x^{k}\log^{k}xdx\\ & =\sum_{k=0}^{\infty}\frac{1}{k!}\int_{\infty}^{0}e^{-ky}\left(-y\right)^{k}e^{-y}\left(-1\right)dy\cmt{x=e^{-y}}\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!}\int_{0}^{\infty}e^{-\left(k+1\right)y}y^{k}dy\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!\left(k+1\right)^{k+1}}\int_{0}^{\infty}e^{-y}y^{k}dy\\ & =\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k}}{k!\left(k+1\right)^{k+1}}k!\\ & =-\sum_{k=0}^{\infty}\frac{\left(-1\right)^{k+1}}{\left(k+1\right)^{k+1}}\\ & =-\sum_{k=1}^{\infty}\frac{\left(-1\right)^{k}}{k^{k}}\\ & =-\sum_{k=1}^{\infty}\left(-k\right)^{-k} \end{align*}

ページ情報

タイトル

2年生の夢(高さ2のテトレーションの0から1までの定積分)

URL

https://www.nomuramath.com/t3qak7ep/

SNSボタン